Analisis Progam Adiwiyata untuk Membentuk Karakter Akhlak Beragama pada P5 di SMA Negeri 1 Tambakboyo - Much.Mahfud Arif; Nining Dewi Anggraeni; Shoidatun Thoyibah (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This research seeks to explore how the Adiwiyata program is implemented in fostering students' religious character through the Pancasila Student Profile Strengthening Project (P5) at SMA Negeri 1 Tambakboyo.The research employed a qualitative method with a phenomenological approach, focusing on exploring the direct experiences of teachers and students in carrying out the program. The data were obtained using observation, in-depth interviews, and documentation techniques. The findings indicate that the Adiwiyata program not only contributes to raising environmental awareness but also plays a significant role in instilling character values such as responsibility, discipline, cooperation, and socio-ecological awareness. These values are internalized through reflective and participatory daily activities, such as classroom cleaning duties, waste management, composting, and energy-saving campaigns. All of these activities are carried out with active and structured involvement from teachers, the school principal, and the entire school community. Supporting factors include adequate facilities and infrastructure, habituation of positive behaviors, and the integration of religious values into environmental activities. However, some challenges remain, such as the low initial understanding of new students and inconsistent behavior change. The implication of these findings is that environmental programs, when integrated with character education, can serve as effective media for building students’ moral and religious values in a contextual and sustainable manner, in line with national education goals and Islamic principles.